1999
DOI: 10.1007/pl00006600
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Close Linkage Between the Genes Encoding Troponin I and Troponin T, Reflecting an Evolution of Adapter Proteins Coupling the Ca2+ Signaling of Contractility

Abstract: Ca(2+)-regulated motility is essential to numerous cellular functions, including muscle contraction. Systems with troponin C, myosin light chain, or calmodulin as the Ca(2+) receptor have evolved in striated muscle and other types of cells to transduce the cytoplasm Ca(2+) signals into allosteric conformational changes of contractile proteins. While these Ca(2+) receptors are homologous proteins, their coupling to the responding elements is quite different in various cell types. The Ca(2+) regulatory system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…We previously detected in ex vivo promoter analysis that the kb Ϫ2.2 to Ϫ5.4 upstream region of the ssTnT gene, which overlaps with the 3Ј region of the cTnI gene, contained major enhancer activity required for high level transcription of the ssTnT gene (6). The present study further demonstrated that deletion of the cTnI gene between the two BamHI sites (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We previously detected in ex vivo promoter analysis that the kb Ϫ2.2 to Ϫ5.4 upstream region of the ssTnT gene, which overlaps with the 3Ј region of the cTnI gene, contained major enhancer activity required for high level transcription of the ssTnT gene (6). The present study further demonstrated that deletion of the cTnI gene between the two BamHI sites (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The cardiac TnI (cTnI) (TNNI3) and ssTnT genes are very closely linked. Shown in ex vivo promoter analysis, the 5Ј upstream enhancer region of the ssTnT gene overlaps with the structure of the cTnI gene (6). This structural integration of cTnI and ssTnT genes suggested that a previously developed mouse line in which the entire Tnni3 gene was deleted through embryonic stem cell gene targeting (7) would have lost a large portion of the 5Ј-enhancer region of the Tnnt1 gene (Fig.…”
Section: Troponin T (Tnt)mentioning
confidence: 94%
See 1 more Smart Citation
“…Genomic Cloning and Sequencing-Genomic DNA was prepared from the liver of domestic turkey by proteinase K digestion and phenol/ CHCl 3 extraction (39). Two oligonucleotide primers were synthesized for PCR amplification of the segment containing the exon 7 to exon 10 region of the turkey cTnT gene.…”
Section: Sds-page and Westernmentioning
confidence: 99%
“…AAVS1 is located 14.9 and 36 kb centromeric to the slow skeletal troponin T (TNNT1) and cardiac troponin I (TNNI3) genes, respectively (12). The mouse Tnni3 and Tnnt1 genes are located on chromosome 7 (13,14), in a region previously shown to be syntenic to the human chromosome 19 region that contains AAVS1 (7). We used the Celera discovery system to search the Celera mouse genome assembly with the mouse Tnni3 and Tnnt1 genes, the AK010836 cDNA, and the human MBS85 genomic sequence.…”
mentioning
confidence: 99%